Surrealismo visceral desarrollo (2017)
"The visceral surrealism evokes the sensation of carrying on the disgust and the fear that has artrosis as part of us, that is, as a second skin, starting from the fact that direct contact with it is the highest degree Reaction negative. From this, use the material of surrealism within the scenario of cognitive behavioral therapy to bring users an experience of a textile that recreates the sensations that evoke their disgust and fear in the lathe controlled elements. Within the sensations manifested is feeling trapped, absorbed, without a notion of reality in terms of size and an unreasonable propagation." -- Tomado del Formato de Documento de Grado.